Spontaneous Rupture of the Omental Artery Treated by Transcatheter Arterial Embolization. (17th December 2012) - Takahashi, Masamichi; Matsuoka, Yujiro; Yasutake, Tsuyoshi; Abe, Hiroyuki; Sugiyama, Kazuhiro; Oyama, Kazuyuki
Abstract : Intra-abdominal hemorrhage caused by omental artery rupture is a rare condition. There are few reports on the treatment of omental artery rupture with only transcatheter arterial embolization (TAE). A 27-year-old man presented to our emergency room with upper abdominal pain that suddenly occurred during sleep. Abdominal computed tomography (CT) revealed fluid collection in the peritoneal cavity and a left subphrenic hematoma with extravasation. Celiac angiography revealed extravasation from the omental artery, which arose from the proximal left gastroepiploic artery. A microcatheter was advanced into the left gastroepiploic artery and around the culprit artery bifurcation, which was embolized by inserting coils. The postoperative course was uneventful without worsening of anemia or abdominal symptoms. The patient was discharged after the absence of extravasation was confirmed by contrast-enhanced CT. Although surgical therapy has often been performed for omental bleeding, TAE, which is less invasive and has the advantage of simultaneous diagnosis and treatment, should be attempted as the first-choice therapy.